2022
DOI: 10.1111/hae.14498
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a self‐induced myofascial release protocol using a foam roller in patients with haemophilic knee arthropathy

Abstract: Background: Haemophilic knee arthropathy presents functional and structural alterations and chronic pain. Self-induced myofascial release aims to treat fascial restrictions and improve functionality.Aim: This study investigated the safety and effectiveness of a self-induced myofascial release protocol in patients with haemophilic knee arthropathy.Methods: Twenty-five patients with bilateral haemophilic knee arthropathy were recruited (n = 50 knees). The patients followed an intervention protocol, with daily ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…More than 40% of patients in our study reported an improvement exceeding the MDC in pressure pain threshold on the external malleolus, tibialis anterior muscle strength and range of motion. These values, although lower than those observed in other studies 45 should be interpreted from a clinical perspective. This intervention based on visualization of movement causes changes due to brain modulation.…”
Section: Discussioncontrasting
confidence: 75%
“…More than 40% of patients in our study reported an improvement exceeding the MDC in pressure pain threshold on the external malleolus, tibialis anterior muscle strength and range of motion. These values, although lower than those observed in other studies 45 should be interpreted from a clinical perspective. This intervention based on visualization of movement causes changes due to brain modulation.…”
Section: Discussioncontrasting
confidence: 75%
“…A recent cohort study 19 has shown the safety of myofascial self-release with foam rolling in patients with hemophilic knee arthropathy. This may be explained by the lower mechanical pressure exerted on the joint since foam rolling releases tension in the fascia.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The use of myofascial self-release exercises has shown its effectiveness in reducing pain in patients with hip osteoarthritis 17 and plantar fasciitis, 18 also improving the range of motion in the latter case. Although a recent cohort study 19 has shown the safety and efficacy of a self-induced myofascial therapy protocol in patients with knee arthropathy, to date there have been no multicenter randomized clinical studies confirming the efficacy of this technique.…”
mentioning
confidence: 99%
“…It was measured in the sagittal plane under no-load pain-free conditions, with the patient in the supine position. The goniometer was positioned with its axis on the joint interline, the reference points being the longitudinal axis of the femur and fibula [ 30 ]. The higher the degrees, the greater the range of motion.…”
Section: Methodsmentioning
confidence: 99%